Effect of Ion Selectivity on Current Production in Sewage Microbial Fuel Cell Separators - Ryoya Itoshiro; Naoko Yoshida; Toshiyuki Yagi; Yuriko Kakihana; Mitsuru Higa (Membranes, 2022)
This study compared the performance of two microbial fuel cells (MFCs) equipped with separators of anion or cation exchange membranes (AEMs or CEMs) for sewage wastewater treatment. Under chemostat feeding of sewage wastewater (hydraulic retention time of approximately 7 h and polarization via an external resistance of 1 Ω), the MFCs with AEM (MFCAEM) generated a maximum current that was 4–5 times greater than that generated by the MFC with CEM (MFCCEM). The high current in the MFCAEM was attributed to the approximately neutral pH of its cathode, in contrast to the extremely high pH of the MFCCEM cathode. Due to the elimination of the pH imbalance, the cathode resistance for the MFCAEM (13–19 Ω·m2) was lower than that for the MFCCEM (41–44 Ω·m2). The membrane resistance measured as the Cl− mobility of AEMs for the MFCAEM operated for 35, 583, and 768 days showed an increase with operation time and depth, and this increase contributed minimally to the cathode resistance of the MFCAEM. These results indicate the advantage of the AEM over the CEM for air-cathode MFCs. The membrane resistance may increase when the AEM is applied in large-scale MFCs on a meter scale for extended periods.